(untitled) - Charan, Ram (New York, 2009)
In Leadership in the Era of Economic Uncertainty, Ram Charan helps you steer your business through the minefi eld of contracting markets, cash shortages, and ongoing uncertainty. No matter what your leadership role, Charan's insight will help ensure that your business emerges leaner, stronger, and well in front of the competition.
Keywords: Leadership,Financial crises,Achievement motivation